In situ study of the tensile deformation micro-mechanisms of semi-crystalline poly(ethylene terephthalate) films using synchrotron radiation X-ray scattering. (19th May 2017) - Donnay, Martin; Ponçot, Marc; Tinnes, Jean-Philippe; Schenk, Thomas; Ferry, Olivier; Royaud, Isabelle
Abstract: Wide - and small-angle X-ray scattering are used to perform in situ experiments with synchrotron radiation. The high X-ray intensity enabled the study of the deformation mechanisms of poly(ethylene terephthalate) semi-crystalline films under tension. Microstructural parameters such as crystallinity ratio, macromolecular orientation, long period, length, width and thickness of crystalline lamellae are measured. A new method to follow macromolecular orientation is detailed. In the elastic-viscoelastic region, lamellae rotate along the tensile axis without increase of orientation parameters. The plastic strain is initiated by crystallographic processes: crystal slip with (010)[001] and (010)[010] systems, flexural breaking of the longitudinal lamellae and separation of (010) planes in transverse lamellae. The plastic flow is the continuation of these processes and the strengthening of the macromolecular orientation in both crystalline and amorphous phases. The shear forces applied to transverse lamellae rotating to a longitudinal orientation make them adopt a tilted shape. Graphical abstract: Highlights: A combined analysis of SAXS and WAXS data for the study of deformation micromechanisms. Measurement of macromolecular orientation, 3D lamellae size and shape. The description and application of a new method to follow macromolecular orientation. Emphasis on several deformation mechanisms in semi-crystalline polymers.